The Influence of Work Environment And Individual Characteristics on Employee Performance Through an Integrative Approach - Muhammad Nur Fahmi Salim; Wiwik Saidatur Rolianah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of the work environment and individual characteristics on the performance of production employees at PT. Jenggong Mulya Jaya Sentosa, Gresik. Using a quantitative approach, the entire population of 29 production employees was sampled using a saturated sampling technique. Information was gathered through a Likert-scale survey and examined using multiple regression analysis in SPSS version 27. 00. Validity and reliability test results indicate that all research instruments are valid and reliable. The classical assumptions (normality, multicollinearity, and heteroscedasticity) were also met, indicating a good regression model. A partial t-test revealed that the work environment (X2) had a significant partial effect on employee performance (Y), with a Sig. value of 0.045. However, human relations (X1) did not show a significant partial effect on employee performance (Y), with a Sig. value of 0.659. Furthermore, the simultaneous test (F test) shows that together, the work environment and human relations do not have a significant influence on employee performance (F count = 2.319 < F table and Sig. = 0.119 > 0.05). Finally, The outcome of the coefficient of determination assessment (Adjusted R Square) of 0. 089 shows that the two independent variables can account for only 8. 9% of the differences in employee performance, while the other 91. 1% is attributed to additional factors not included in the research model. This study concludes that although the work environment is individually important, further exploration is needed on other factors that influence employee performance at PT. Jenggong Mulya Jaya Sentosa to achieve optimal production results.